Analysis of Deixis in The Short Story Beauty and The Beast - Ines Alevia Sandoval; I Gusti Ngurah Parthama; Nissa Puspitaning Adni (JLER (Journal of Language Education Research), 2024)
This study conducts an analysis of deixis within selected excerpts from "Beauty and the Beast," aiming to explore how deixis contributes to the construction of meaning and narrative coherence in the story. Through a close examination of first-person, second-person, and third-person deixis, as well as time, place, discourse, and social deixis. The data was taken from the short story Beauty and the Beast. This analysis used Levinson theory in categorized types of deixis. The qualitative descriptive method was used to analyze the data. The data analyzed step were read whole text, classified and analyzed based on the theory. This study found that there were five types of deixis in the short story Beauty and the Beast. There are person deixis, place deixis, time deixis, discourse deixis, and social deixis. This study also highlights the significance of deixis in shaping the narrative structure, character dynamics, and thematic developments within Beauty and the Beast, underscoring the intricate interplay between language and storytelling in literary discourse.